y = x^2 + 2x...eqn 1
y = 3x + 20...eqn 2
subst for y in eqn 1...
=> x^2 +2x = 3x +20
=> x^2 - x - 20 =0
=> (x-5) (x+4) =0
=> x = 5 or -4
for x =5, y = 35 (sub for x in eqn 1 or 2)
for x = -4, y = 8 (sub for x in eqn 1 or 2)
<span>–1 + 6(–1 – 3x) > –39 – 2x.
</span>-1-6-18x>-39-2x
-7-18x>-39-2x
-18x>-32-2x
-16x>-32
x<2
B. x<2
Answer: $9 per hour at his job as a cashier and $8 per hour at his job delivering newspapers.
Step-by-step explanation:
1. Let's call the amount he got paid per hour at his job as a cashier: .
Let's call the amount he got paid per hour at his job delivering newspapers: .
2. Keeping on mind the information given in the problem above, you can make the following system of equations:
3. You can solve it by applying the Substitution method, as following:
- Solve for one of the variables from one of the equations and substitute it into the other equation to solve for the other variable and calculate its value.
- Substitute the value obtained into one of the original equations to solve for the other variable and calculate its value.
4. Therefore, you have:
Then:
Finally:
Therefore he got paid $9 per hour at his job as a cashier and $8 per hour at his job delivering newspapers.
The correct answer is A.
Horizontal shift is obtained by addition/subtraction a number to every occurrence of x in the equation. Addition indicates a shift towards left and subtraction indicates a shift towards right.
So the correct answer is Subtract that number From.